Impacts of Agrobiodiversity in Landscape Ecology - Hailu, Fekadu (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
The agricultural landscape is very important for the production of goods and services, which are vital to human life. However, agricultural intensification affects the ecological interconnection, function, structure, and capability of landscape production and productivity. Therefore, this review aims to understand the role, diverse causes of biodiversity losses, and maintenance options of agrobiodiversity in landscape ecology. To achieve these objectives, different reputable journal articles that were published starting in 2013 until now were collected, organized, summarized, and compiled carefully. Agrobiodiversity includes all the components of biological diversity that are relevant to agricultural ecosystems. It has an essential role in the sustainable development of agricultural systems, which provide food, fiber, fuel, fodder, medicines, and other products for subsistence. Agricultural biodiversity has a great contribution to food security, production, environmental sustainability, diversifying rural livelihoods, and rural development. These essential agrobiodiversity are endangered due to the ignoring of native knowledge, the absence of local institutions and management systems, inequitable tenure, market pressures, and demographic factors. Thus, conserving agrobiodiversity and its multiple functions included awareness creation in ecosystem management, promoting local adaptive management, supporting local participation, strengthening local rights and tenure property, improving trade-related policies, and providing economic incentives.